BASLAWÍSh KLASSLARDA GEYMIFIKACIYADAN PAYDALANÍP OQÍWShÍLARDÍŃ DÓRETIWShILIGIN RAWAJLANDÍRÍW - Zarımbetova, G.K. (SCIENCE and SOCIETY, 2025)
The article deals with the need to improve the level of knowledge of primary school pupils, the need to carry out work on the mutual harmonization of education and life in the form of a game, and the use of modern gamifications, the opportunity to improve intellectual level, work in a team and acquire skills that are interconnected with the real worl